2017
DOI: 10.1002/cncr.30918
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer of the Bladder Risk Assessment (COBRA) score: Estimating mortality after radical cystectomy

Abstract: The COBRA score offers a straightforward, validated risk-stratification tool that incorporates the relative contribution of tumor stage and lymph node involvement to patient prognosis after cystectomy for UCB. Cancer 2017;123:4574-4582. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 32 publications
0
49
0
1
Order By: Relevance
“…A prior study of UC reported no gender differences in the histopathological characteristics of the tumor [ 25 ]. And more recently, Welty et al developed a new nomogram to predict UC survival following surgery, based on the tumor characteristics, and did not include sex as a prognostic factor [ 4 ]. Our study is the first to investigate gender differences in the grade or the stage of the SCC type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior study of UC reported no gender differences in the histopathological characteristics of the tumor [ 25 ]. And more recently, Welty et al developed a new nomogram to predict UC survival following surgery, based on the tumor characteristics, and did not include sex as a prognostic factor [ 4 ]. Our study is the first to investigate gender differences in the grade or the stage of the SCC type.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, to predict recurrence of bladder cancer after surgery, the International Bladder Cancer Nomogram Consortium (IBCNC) developed a tool that includes, among other variables, sex, cancer histological type, and characteristics, as prognostic factors [ 3 ]. However, Welty et al developed a nomogram to predict survival after cystectomy for urothelial cell carcinoma, but did not include sex, because they found age and tumor stage to be considerably stronger risk factors than sex in predicting patient survival [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lymph node (LN) density has been identified as a better prognostic marker than nodal staging, and is calculated by dividing the total number of positive resected LNs by the total number of resected LNs [6–8]. The Cancer of the Bladder Risk Assessment (COBRA) score was developed to predict cancer‐specific mortality (CSM) after surgery and was based on the Surveillance, Epidemiology, and End Results (SEER) cancer database [9]. The COBRA score is calculated using three variables: age at RC, tumour stage, and LN density.…”
Section: Introductionmentioning
confidence: 99%
“…The COBRA score is calculated using three variables: age at RC, tumour stage, and LN density. The COBRA score ranges from 0 to 7, and each point increase is associated with a 1.61‐fold increase (95% CI 1.56–1.65) in the risk of CSM [9]. The COBRA score can be used to counsel patients more adequately on their cancer‐specific prognosis after RC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation